Perspectives of public sector entrepreneurship and change agents in village tourism management - Kadun MT, Alienra Davry Nanda; Nurjaman, Rahmat; Nunes, Mariano (Universitas Islam Malang, 2025)
As the only developed tourism village in Papua, Yoboi Village exemplifies successful tourism village management. Given its outstanding performance, this study aims to examine the role of change agents and the contribution of public sector entrepreneurship towards the management of village tourism. Researchers used Caldwell’s framework to identify change agents roles consisting of champions, adapters, consultants, and synergists, meanwhile the PSE concepts asserting the public officials roles to produce public value. Using a qualitative approach through case study method, researchers collect data through interviews, focus group discussion, observations, and documentation. The research’s findings describe the active engagement of the village’s youth reflects the concept of change agents aligns with the role as champion. Additionally, the active participation of a key local figure also serving as a public official in Jayapura regency illustrates the public actor participation which also fit with the public sector entrepreneurship principle. This study emphasizes the dynamic role of a key actor, whose leadership emerged not solely from individual competencies but was also significantly influenced by contextual and environmental factors. The combination of attributes from both the change agent and public sector entrepreneurship paradigms have contributed to Yoboi village tourism success.